Analisis Makna Pesan Simbolik Penyandang Oligodaktili Dusun Ulutaue di Kabupaten Bone - Ismi Amir Ismi; Andi Alimuddin Unde; Tuti Bahfiarti (Universitas Serang Raya, 2022)
ABSTRACT People with oligodactyly are humans who have less than five fingers and toes. This deficiency is formed since their birth. This study involved five informants from Ulutaue Hamlet, Bone Regency of South Sulawesi Province, Indonesia. People with oligodactyly usually get the nicknames